APB farewell lunch for Dr. Angel Helen Pereira - Yeo, Jiin Yih (UiTM Sarawak, 2016)
Akademi Pengajian Bahasa (APB) UiTM Sarawak organised a farewell lunch for one of its lecturers, Dr Angel Helen on 23rd October 2015 at the Summer Mall, Kota Samarahan. Dr Angel Helen retired after a fourteen-year stint in UiTM Sarawak.